THE ROLE OF SHORT VIDEO MARKETING, ELECTRONIC WORD OF MOUTH, AND PERCEIVED RISK IN BUILDING CONSUMER TRUST AND PURCHASE INTENTION IN ONLINE TRAVEL AGENTS - Firdausa, Faza Ruziqyani; Suhud, Usep; Berutu, Meta Bara (Yayasan Education and Social Center, 2025)
This study aims to examine and analyze the role of short video marketing, electronic word of mouth, and perceived risk in building consumer trust and purchase intention in online travel agents. This study involved 252 respondents who had seen Tiket.com service promotions on social media and were domiciled in Jakarta. The analytical methods used were validity and reliability testing using SPSS software, model feasibility testing, and hypothesis testing using AMOS 29 software. The analysis technique used was Structural Equation Modeling. These findings indicate that short video marketing and eWOM increase consumer trust, but only eWOM significantly drives purchase intention. Short video marketing does not directly influence purchases, while perceived risk does not reduce consumer trust but instead drives purchase intention because consumers are more cautious. Consumer trust itself is not significant for purchase intention, so other factors such as price and promotions remain important in purchasing decisions.